Support for a Long Lifetime and Short End-to-End Delays with TDMA Protocols in Sensor Networks - Marcin Brzozowski; Hendrik Salomon; Peter Langendoerfer (International Journal of Distributed Sensor Networks)
This work addresses a tough challenge of achieving two opposing goals: ensuring long lifetimes and supporting short end-to-end delays in sensor networks. Obviously, sensor nodes must wake up often to support short delays in multi-hop networks. As event occurs seldom in common applications, most wake-up are useless: nodes waste energy due to idle listening. We introduce a set of solutions, referred to as LETED (limiting end-to-end delays), which shorten the wake-up periods, reduce idle listening, and save energy. We exploit hardware features of available transceivers that allow early detection of idle wake-up periods. This feature is introduced on top of our approach to reduce idle listening stemming from clock drift owing to the estimation of run-time drift. To evaluate LETED and other MAC protocols that support short end-to-end delays we present an analytical model, which considers almost 30 hardware and software parameters. Our evaluation revealed that LETED reduces idle listening by 15x and more against similar solutions. Also, LETED outperforms other protocols and provides significant longer lifetimes. For example, nodes with LETED work 8x longer than those with a common TDMA and 2x-3x longer than with protocols based on preamble sampling, like B-MAC.